The future of patient safety in Ghana: challenges and opportunities - Augustine Kumah (Frontiers in Health Services, 2025)
Patient safety is a critical aspect of healthcare that ensures the reduction of preventable harm to patients during the provision of care. Patient safety has recently gained increasing attention in Ghana, but significant challenges remain. These include inadequate healthcare infrastructure, workforce shortages, medication errors, hospital-acquired infections, and poor reporting and monitoring systems. Moreover, limited public awareness and weak regulatory enforcement exacerbate patient safety risks. However, Ghana also has several opportunities to improve patient safety. Adopting digital health solutions, investing in healthcare worker training, strengthening regulatory frameworks, and community engagement present promising pathways for progress. The government's commitment to Universal Health Coverage (UHC) and recent healthcare policy reforms provide an enabling environment to enhance patient safety initiatives. This article explores the future of patient safety in Ghana by examining key challenges and potential opportunities. It provides an in-depth analysis of patient safety, discusses barriers to improvement, and highlights strategies to enhance safety outcomes. The article also examines global best practices that can be adapted to the Ghanaian healthcare system. Improving patient safety in Ghana requires a multi-stakeholder approach, integrating policy reform, technology, workforce development, and public awareness campaigns. By leveraging existing opportunities and addressing challenges, Ghana can move toward a safer, more effective healthcare system that protects patients from preventable harm.